2021
DOI: 10.1002/aur.2621
|View full text |Cite
|
Sign up to set email alerts
|

Job loss predicts worsening depressive symptoms for young adults with autism: A COVID‐19 natural experiment

Abstract: Adults with autism spectrum disorder (ASD) experience high rates of both unemployment and depression. Though job loss predicts increased risk of depression in the general population, studies have yet to directly examine this relationship among individuals with ASD. With the backdrop of rising unemployment due to COVID‐19, we used a longitudinal design to examine whether employment changes predicted increasing depressive symptoms among young adults with ASD. Online surveys were collected from young adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Furthermore, unexpected disruptions in employment are another source of distress associated with mental health problems for adults on the autism spectrum, highlighting the importance of job security (Müller et al, 2003). Two recent studies on employment changes during the COVID-19 pandemic provided direct evidence of the negative impact of a job change or loss on psychological well-being and mental health, as related to workplace satisfaction (Goldfarb et al, 2022;Taylor et al, 2022). Previous studies in this area, together with our findings, suggest that supports are needed and helpful at different stages of employment (Baldwin et al, 2014;Hedley et al, 2017;Hendricks, 2010).…”
Section: Negative Emotional Experiences and Poor Mental And Physical ...mentioning
confidence: 99%
“…Furthermore, unexpected disruptions in employment are another source of distress associated with mental health problems for adults on the autism spectrum, highlighting the importance of job security (Müller et al, 2003). Two recent studies on employment changes during the COVID-19 pandemic provided direct evidence of the negative impact of a job change or loss on psychological well-being and mental health, as related to workplace satisfaction (Goldfarb et al, 2022;Taylor et al, 2022). Previous studies in this area, together with our findings, suggest that supports are needed and helpful at different stages of employment (Baldwin et al, 2014;Hedley et al, 2017;Hendricks, 2010).…”
Section: Negative Emotional Experiences and Poor Mental And Physical ...mentioning
confidence: 99%
“…The adult autistic community report similar adverse outcomes including increased anxiety, depression, loss of social support systems, worries about losing social skills with less social interaction, loss of regular care services, and added communication challenges with remote service provision [27,28]. Additionally, Taylor et al [29] found that a large portion of autistic adults has changed employment status (e.g., loss of job, reduced hours) during the pandemic which in turn was associated with depressive symptoms.…”
Section: Introductionmentioning
confidence: 96%
“…In the general population, negative events such as a job loss predict higher rates of depression, anxiety, stress and loneliness (Andreeva et al, 2015 ; Eckhard, 2020 ; Eersel et al, 2020 ; Hortulanus et al, 2006 ; Libby et al, 2010 ; Stolove et al, 2017 ). Longitudinal studies in autism samples also show negative mental health impacts of job loss (Goldfarb et al, 2022 ; Taylor et al, 2022 ), but no studies to our knowledge have examined the impacts of employer-initiated terminations in this group. Given the high rates of internal attributions in this sample, and the strong associations of internal attributions (vs. external) with self-esteem and self-worth (Wiener, 1985 ), it may be that employer-initiated terminations play a particularly powerful role in influencing psychological health among autistic adults.…”
Section: Discussionmentioning
confidence: 99%